Aleš Žiga Dolničar in knjige o Beneški republiki - Vidmar, Luka (Knjižnica, 2011)
Purpose: the paper deals with manuscripts and books of Aleš Žiga Dolničar and other members of the Baroque Academia operosorum (Accademy of the Industrious) in the Seminary Library in Ljubljana, related to the Republic of Venice. Especially it examines the prints that influenced Dolničar's manuscript Descriptio nobilissimae urbis Venetiae (1703), including description of a travel from Gorizia to Venice, panegyric on Venice, descriptions of some important churches, and lots of drawings. At the end it reconstructs his relations with political, religious, and artistic heritage of the Serenissima. Methodology/approach: the historical method, based on a critical source study. Results: new findings about Aleš Žiga Dolničar and the Academia operosorum established throughout the study of up till now unresearched sources. Research limitation: manuscripts and books in the Seminary Library in Ljubljana. Originality/practical implications: original contribution to the history of Baroque culture in Carniola.
Keywords: Dolničar, Aleš Žiga, 1685-1708; manuscripts; rokopisi; books; stare knjige; Academia operosorum; Akademija operozov; Seminary library (Ljubljana); Venice (Italy); Semeniška knjižnica (Ljubljana); Baroque; Benetke (Italija); kulturna zgodovina; barok